Enhanced selectivity in alpelisib quantification in human plasma: a validated LC-MS/MS method with deuterated internal standard - Venkateswararao Agraharapu; Venkata Rao Vutla; Vidyadhara Suryadevara (Creative Pharma Assent, 2026)
Background: To enhance efficacy and manage dose-limiting toxicities such as hyperglycemia, therapeutic drug monitoring of alpelisib (ALB), a phosphatidylinositol 3-kinase alpha (PI3Kα) inhibitor used in advanced breast cancer, is essential. This study aimed to develop and validate a selective, sensitive, and high-throughput liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the quantification of ALB in human plasma to support pharmacokinetic studies and therapeutic drug monitoring. Methodology: Alpelisib-D3 was used as a deuterated internal standard (IS). Analytes were extracted from 50 µL of plasma by liquid-liquid extraction using n-hexane and methyl tert-butyl ether (20:80, v/v). Chromatographic separation was performed on an X-Terra RP8 column using an isocratic mobile phase of 5 mM ammonium acetate buffer (pH 5.00) and acetonitrile (10:90, v/v) at 0.4 mL/min. Detection was carried out in positive electrospray ionization mode using multiple reaction monitoring of m/z 442.15→141.07 for ALB and m/z 445.36→144.05 for the IS. Validation included linearity, precision, accuracy, recovery, matrix effect, carryover, dilution integrity, and stability. Results and discussion: The method was linear over 50.0–10,000 ng/mL. Intra- and inter-day precision (CV%) was <4.2%, and accuracy ranged from 94.5% to 106.2%. Mean extraction recovery exceeded 90%, with no significant matrix effects. Carryover, stability, and dilution integrity also met acceptance criteria. Conclusion: A reliable, sensitive, and selective LC-MS/MS method was successfully developed and validated. The method is suitable for high-throughput pharmacokinetic studies and therapeutic drug monitoring of ALB in human plasma.